The Effect of PVP Concentration on Particle Size, Morphological and Optical Properties of Cassiterite Nanoparticles - Al-Hada N.M.; Al-Ghaili A.M.; Kasim H.; Saleh M.A.; Flaifel M.H.; Kamari H.M.; Baqiah H.; Liu J.; Jihua W. (Institute of Electrical and Electronics Engineers Inc., 2023)
Fourier transform infrared spectroscopy; Nanoparticles; Particle size; Silicon compounds; Solar energy; Anti-bacterial activity; Calcination temperature; Growth of particles; High purity; PL spectroscopy; Polyvinyl pyrrolidone; Structural and morphological properties; TEM images; Optical properties